ANALISIS NIAT UNTUK MENGGUNAKAN APLIKASI BELLA DENGAN PENDEKATAN TECHNOLOGY ACCEPTANCE MODEL - Widyawati, Filla; Handayani, Wahyu Prabawati Putri (Surakarta Management Journal, 2022)
This study aims to analyze the effect of Usability and Ease of Use to the Intention of using the Bella Application for a Permanent Lecturer at the Widya Mandala Surabaya Catholic University at Madiun. The samples are all permanent lecturers at the Widya Mandala Surabaya Catholic University at Madiun, with a total of 56 respondents. By using saturated sample method, from 56 respondents, we only processed 42 questionnaires because there were 14 questionnaires that did not return. Data was collected by using a 5-point Likert scale. We used multiple linear regression analysis with SPSS Version 22 program as a tool. The results showed that the usability variable had a positive and significant effect on the intention of use and the ease of use variable had a positive and significant effect on the intention to use.